Chikungunya Encephalomyeloradiculitis: Report of 2 Cases with Neuroimaging and 1 Case with Autopsy Findings - Ganesan, K.; Diwan, A.; Shankar, S.K.; Desai, S.B.; Sainani, G.S.; Katrak, S.M. (American Journal of Neuroradiology, 2008)
SUMMARY: Chikungunya, an alphavirus presenting with fever, rash, and polyarthritis, is derived from the Makonde word that means “that which bends up,” in reference to the crippling manifestations of the disease. Most often it is a self-limiting febrile illness. Neurologic complications of Chikungunya infection have been reported. We are reporting the clinical and neuroimaging data in 2 patients with Chikungunya encephalomyeloradiculitis and brain autopsy findings in 1 patient.